Pengaruh Likuiditas, Solvabilitas, dan Kebijakan Dividen Terhadap Nilai Perusahaan Sebagai Keputusan Investasi Dalam Perspektif Ekonomi Islam - Alda Sophie (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The company value which is always closely related to the stock price, is a point of view or investors in seeing the success of a company. The high or low value of the company can be caused by several factors that can influence investors decisions in making investment decisions. Thereore it is necessary to test to find out what factors can be affect the value of the company. This study aims to determine the effect of liquidity, solvency and dividend policy on company value, which is then carried out by stock valuation to assist investors in making investment decisions in Consumer Goods Companies lited on JII in 2012-2021. The results of study show that liquidity has a significant positive effect on firm value, meaning that companies that are able to pay debts on time can increase firm value. Solvability has a significant positive efect on firm value, meaning that the company has good credibility from the point of view of investors thereby increasing firm value. Dividend policy has a significant positive efect on firm value. Liquidity, solvency, and dividend policy have a positive effect on firm value because the higher the firm value, the greater the conidence of investors to invest in the company. Islamic economic principles can be used as a basis for investors and issuer who wish to implement sharia investment. The results of the stock valuation show that the average stock is classified as overvalued. The recomended investment decision is to sell the shares.